ISLAMIC CIVILIZATION, PERIODIZATION, AND DEVELOPMENT IN INDONESIA AND SPAIN AND THEIR EFFECT ON WESTERN CIVILIZATION: A HISTORICAL REVIEW - Asmamatin, Renata; Ferianto, Ferianto (Riviera Publishing, 2023)
This study aims to depict the Islam’s history of development and Islamic civilization from its propagation to the present. The descriptive qualitative research approach utilized in developing this study intends to describe the development and civilization of Islam. A literature review collects data from numerous sources such as books, journals, papers, articles, and electronic media such as the Internet. The writer also employs qualitative data analysis and the deductive writing style in this study. The findings show that some of the basics of Islamic civilization proposed by Prophet Muhammad that can be known; mosque building, forming the ukhuwah islamiyah, and building relationships between non-Muslims. Therefore, during this civilization, one of the famous scholars, Nourouzabad ash-Shiddiqi, states that the periods are committed to two periodizations; the classical period of Islam (650-1250), a period of Islamic progress, and a time of disintegration modern period of Islam (1800-today) is marked by the rise of Islam in politics, military, social, and cultural spheres and the revival of philosophical thinking among some of the Arab scientists.